The deconvolution of thermoluminescence glow-curves using general expressions derived from the one trap-one recombination (OTOR) level model. (January 2015) - Sadek, A.M.; Eissa, H.M.; Basha, A.M.; Carinou, E.; Askounis, P.; Kitis, G.
Abstract: The new developed thermoluminescence (TL) glow-peak expressions derived from the one trap-one recombination (OTOR) level model were used to analyze the TL glow-curves recorded with linear and exponential heating function profiles under various experimental conditions. The results showed that these expressions can, accurately, analyze the TL glow-curves even with the overlapped glow-peaks. Low values of R = A n / A m were reported for glow-peaks in different TL materials. A glow-peak with the possibility of A n > A m was also pointed out. Highlights: The accuracy of the TL expressions derived from the OTOR model was verified. EHF and LHF glow-curves were deconvoluted using TL expressions based on OTOR model. Low values of R = A n / A m were reported for some glow-peaks. A glow-peak with the possibility of A n > A m was pointed out.